Application of Realistic Mathematic Education (RME) Approach in learning Mathematic to Improve Student Learning Outcomes - Purwati, Ratna (International Conference on Elementary Education, 2020)
The study is motivated low value math test results on material the principal fragments, it marked the average value of repeat students who are still at the bottom of the KKM with 20 students who did not reach the KKM. Based on these problems, the aim of the research is to describe implementation of the realistic mathematic education approach in planning, implementation and increase student learning outcome in mathematics learning in class V matter fractions in SDN 3 Cibodas.This research used classroom action research, which adapts the Kemmis & Mc. Taggart with three cycles. The techniques of collecting data were observation and test. The result of research indicated the score of cognitive in cycle I got 67,73, increase in cycle II became 76,92 and in cycle III got 82,76. In the affective students when doing LKS in their groups with a percentage of cycle I 64.90 % cycle II Increased 71.85% and cycle III reached 77.08%. Based on the above research results it can be concluded that the use of the Realistic Mathematic Education model can improve student learning outcomes in mathematics with fraction subject matter